ANALYSIS OF THE IMPLEMENTATION OF PAPERLESS AND E-BILLING SYSTEMS IN THE FIELD OF SERVICE AND VERIFICATION OF TRAVEL DOCUMENTS - Mila Rosmaya; W Wilonotomo; Rully Novan Ripsandi Ohei (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
The paperless system discussed in this research is a system applied to the sector of travel document service and verification that replaces the paper-based form containing applicant’s data into a digital form. E-billing system discussed in this research is the actualization of paperless system mentioned earlier. This system replaces the paper- based payment billing to the digital payment billing. The e-billing is sent to the applicant by short messages service. This research analyzes the implementation of paperless and e- billing systems in travel documents service and discovers the corporate image of the West Jakarta Special Class I of Non Checkpoint Immigration Office formed through the implementation of paperless and e-billing systems. The research method used is a descriptive qualitative method. The analysis involves paperless theory and corporate image theory to answer and analyze the problems in this research. The technique of data collection comprises a semi-structured interview, observation and documentation. Data processing and analysis techniques refer to Miles and Huberman’s concept. The results of this research show usefulness of the paperless and e-billing system that has been implemented in the process of travel documents service as well as portrays the positive corporate image of the West Jakarta Special Class I of Non Checkpoint Immigration Office established by implementing the paperless and e-billing system.